A
[tex] \frac{1}{9} + \frac{7}{9} = \frac{1 + 7}{9} =\frac{8}{9} \\ \\ \frac{3}{9} + \frac{7}{9} = \frac{3 + 7}{9} = \frac{10}{9} = 1 \frac{1}{9} \\ \\ \frac{2}{9} + \frac{7}{9} = \frac{2 + 7}{9} = \frac{9}{9} = 1 \\ \\ \frac{6}{9} + \frac{7}{9} = \frac{6 + 7}{9} = \frac{13}{9} = 1 \frac{4}{9} [/tex]
B
[tex] \frac{9}{6} - \frac{3}{6} = \frac{9 - 3}{6} = \frac{6}{6} = 1 \\ \\ \frac{5}{6} - \frac{3}{6} = \frac{5 - 3}{6} = \frac{2}{6} {}^{ \div 2} = \frac{1}{3} \\ \\ \frac{6}{6} - \frac{3}{6} = \frac{6 - 3}{6} = \frac{3}{6} {}^{ \div 3} = \frac{1}{2} \\ \\ \frac{4}{6} - \frac{3}{6} = \frac{4 - 3}{6} = \frac{1}{6} [/tex]
…ᘛ⁐̤ᕐᐷฅ^•ﻌ•^ฅ